Systematic Literature Review on the Implementation of the Pesantren Muadalah Certificate Policy in Indonesia - Muzayana, Iktafi (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This research explores how Islamic boarding schools are implementing and responding to the modern education system introduced by the Government through the equalization policy (mu'ilah). Considering the vast amount of existing research, a review is necessary to categorize the literature, ensuring the information is clearly and easily understood. The paper applies the Systematic Literature Review (SLR) method, focusing on public policy implementation studies from 2019 to 2023. The SLR process includes defining Research Questions (R.Q.), setting Inclusion and Exclusion Criteria, and conducting Quality Assessments (QA). The findings reveal that the Mujadi diploma policy has been aligned with the Government's formal school diploma. Islamic boarding schools issuing Mujadi diplomas are referred to as Islamic Boarding Schools, specifically those that run Muilah Education Units (SPM). Based on both the supporting and inhibiting factors identified from various sources, the Mujadi policy has proven to be effective in its implementation within the Mujadi Islamic boarding schools.